Annual abundance of salps and doliolids (Tunicata) around Gorgona Island (Colombian Pacific), and their importance as potential food for green sea turtles - Sampson, Laura (2014)
Gorgona National Park protects fertile waters that support large vertebrates, including green sea turtles (Chelonia mydas), and for them, gelatinous zooplankton constitute a food resource that can be found year-round in Gorgona Island´s coastal waters. This study was carried out to determine the abundance of salps and doliolids around Gorgona Island over a year, and to determine whether this is a resource that could be used reliably year-round by green turtles and other large plankton-feeding predators. The monthly abundance of salps and doliolids at eight coastal stations around Gorgona Island (Colombian Pacific) was determined between September 2005 and August 2006. Oblique tows were carried out from 50m to the surface, total zooplankton biomass was measured and the number of salps and doliolids per tow, and frequency of occurrence per station and month were determined. Superficial and bottom sea temperature, superficial and bottom salinity, and chlorophyll-a concentration were recorded at each station. There were tunicate abundance peaks in September 2005 and March 2006. The high abundances in March were probably due to a cold water intrusion into the study area, which resulted in colder saltier water and a shallower thermocline. Tunicates were probably advected to the area by currents from the southwest and aggregated due to the underwater topography. In September, the influence of continental river discharge as well as inputs from rainfall over the island could have provided increased nutrients and resulted in higher abundances. The large filter-feeding vertebrates that feed on tunicates include green sea turtle juveniles, which use coastal waters of Gorgona Island as feeding grounds, as part of their migration route in the Eastern Tropical Pacific. These turtles could be using tunicates opportunistically, as a sporadic resource that is available at certain times of the year. Rev. Biol. Trop. 62 (Suppl. 1): 149-159. Epub 2014 February 01.